EFL Students Responses’ to Online Corrective Feedback in the Teaching of Academic Writing during the Covid-19 - Silsilya Wahyu Nurya; Peptia Asrining Tyas (Journal of English Language and Education, 2022)
During covid-19 pandemic, online learning is one of the alternatives that can be used by the lecturer in carrying out learning. This study aims to analyze the students' response to corrective feedback given by the lecturer during online learning. The research methodology used is a quantitative survey design. The research subjects are 140 student academic writing classes from the 2020 batch of the English Language Education Program in Universitas Brawijaya.  The instrument used is questionnaires filled out online by students. They were 17 questions in four section that were distributed to investigate: 1) collecting personal information and types of online platforms used to provide corrective feedback, 2) the identification the types of error to be corrected from the student’s responses, 3) students’ responses for technique the lecturers should correct their errors, 4) students’ responses to corrected errors by the lecturer. There were 106 responses received (88 female and 18 male students). Based on the results, overall online corrective feedback conducted by the lecturer in academic writing classes has a positive response in the midst of the Covid-19 pandemic situation. Most students find the online corrective feedback in their academic writing class useful during pandemic Covid-19.